The Postmodernist Approach in the Geography of Tourism - Inevitable and/or Fashion? - Kowalczyk, Andrzej (Turyzm/Tourism, 2006)
Traces of the postmodernist approach in geography can also be found in tourism geography. The ambiguity of the term ‘tourism', differing tourist behaviours and motivations etc., as well as the methodological weakness in tourism geography (largely resulting from this and from the lack of appropriate statistical data) lead researchers to take a postmodernist approach, not only because it is in fashion, but also because it is necessary.